Interpretation of General Terms and Emerging Developments; A Comparative Study of Imami Jurisprudence and American Law - Reza Pourmohammadi; Rahim Nobahar (پژوهش تطبیقی حقوق اسلام و غرب, 2022)
How do new technologies affect the way we interpret legal texts? This is, on its face, an enormous question. Technology and science are ever-expanding in a rapid pace but, legislatures are often one step behind. This fact raises an important question: How do emerging developments in science and technology affect the way we interpret legal texts? One could fill many volumes in an effort to engage this issue in a serious way. But we can also learn a great deal about the larger subject by asking a more modest question: Can general old terms cover emerging developments that did not exist before? In this article, we, firstly, show applying general terms to emerging developments is an accepted method in Imami jurisprudence and American law. Secondly, a distinction must be made between emerging developments that could not have been dreamed of before or seemed impossible and emerging developments that could have been anticipated by an ordinary man.